Análisis de una plataforma logística internacional en Colombia - Casadiego, Anderson (Universidad Antonio Nariño, 2021)
The operation of the logistics platform has a determining factor within the competitiveness of a country. Which allows the exponential development of the processes and that are carried out in the best way, the logistics platforms appear, which have with all an infrastructure necessary to satisfy the needs of clients and providers of services related to the supply chain. To this end, it is necessary to retake the foundations of the logistics concept to establish the reasons why the development of an international platform and its implementation in Colombia becomes extremely indispensable in achieving the main objectives looking for logistics in the different areas in which it is used. It is important to denote the incursion mechanisms of any logistic model, analyze the goals and expectations that allow to show how spaces should be created that favor the optimal management of processes such as acquisition, movement, storage, flows and inventories, distribution channels, among others, that would determine the success of the use of a good logistics platform. It will be analyzed how the different international platforms in Colombia offer something more beyond that the simple optimization of the logistics exercise to knowledge that conceptually there would be substantial improvements in all three operational areas; materials management (GM) that refers to the relationship between a company and its suppliers, the management of transformation (GT) which is nothing more than the logistical relationship between the facilities of the company and physical distribution management (GDF) which is situated as the relationship between company and its customers. That is why the object of this analysis where it is intended to show the pros and cons of the need to implement port logistics platforms in Colombia making use of the resources that the country has. Factors such as industrial globalization and international exchanges that are increase above all in the same economic diversity of the intervening countries supports the need to have logistical spaces to meet the demand for services that allow generating greater competitiveness for both companies and the country same, these logistics activities in most Latin American countries and in development, especially in Colombia, the central theme of this document needs develop, since they are scattered and with inconveniences to be measured and Colombia is below the standards of other countries.